Quality control of Semen Hoveniae by high‐performance liquid chromatography coupled to Fourier transform‐ion cyclotron resonance mass spectrometry. Issue 18 (31st July 2021) - Zhang, Qingyu; Xu, Ke; Zhang, Yu; Han, Jing; Sui, Wenwen; Zhang, Haotian; Yu, Maomao; Tong, Yichen; Wang, Sijie; Han, Fei
Abstract: A method based on high‐performance liquid chromatography and Fourier transform‐ion cyclotron resonance mass spectrometry was developed to control the quality of Semen Hoveniae . First, the chromatographic fingerprint was established in combination with the chemometrics methods such as similarity analysis, cluster analysis, principal component analysis, and orthogonal partial least squares discriminant analysis to discover the qualitative markers. Then, an high‐performance liquid chromatography mass spectrometry method was developed to identify the chemical constituents in Semen Hoveniae . Moreover, the content of dihydromyricetin and dihydroquercetin in Semen Hoveniae were determined by high‐performance liquid chromatography. As a result, nine common peaks were assigned in the fingerprints and the similarity of the 13 batch samples varied from 0.425 to 0.993, indicating an obviously different quality. Dihydromyricetin and dihydroquercetin were the main qualitative markers to differ the quality of Semen Hoveniae . Meanwhile, a total of 21 chemical compounds were characterized by high‐performance liquid chromatography mass spectrometry and six of them were identified by comparing with information of reference standards. Finally, the content of dihydromyricetin and dihydroquercetin in 13 batch samples varied from 0.824  to 7.499 mg/g and from 0.05941  to 4.258 mg/g, respectively. In conclusion, the methods developed here will provide sufficient qualitative and quantitative information for the quality control of Semen Hoveniae .